1986
DOI: 10.1128/jb.168.1.365-373.1986
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the genes coding for two major cell wall proteins from protein-producing Bacillus brevis 47: complete nucleotide sequence of the outer wall protein gene

Abstract: BaciUus brevis 47 contains two cell wall proteins termed the outer wall protein (OWP) and middle wall protein (MWP), each of which forms hexagonal arrays in the cell wall. A 6-kilobase Bglll-Bcll fragment of B. brevis 47 DNA cloned into BaciUus subtilis with a derivative of pHWl as a vector directed the synthesis of a polypeptide, with almost the same molecular weight as the authentic OWP, as judged by sodium dodecyl sulfate-polyacrylamide gel electrophoresis, which was specifically recognized by the anti-OWP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
1

Year Published

1992
1992
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 51 publications
1
55
1
Order By: Relevance
“…Clostridium perfringens (Takumi et a/., 1991), the S-layer is composed of more than one protein. In other organisms, such as Aquaspirillum serpens (Kist and Murray, 1984), Clostridium difficile (Kawata et a/., 1984) and B. brevis (Tsuboi et a/., 1986), there appear to be two superimposed S-layers. In other bacteria, including Bacillus stearothermophilus and Campylobacter fetus (Tummuru and Blaser, 1993), more than one S-layer can appear sequentially.…”
Section: Oligonucleotide Probe and Dna Librariesmentioning
confidence: 99%
“…Clostridium perfringens (Takumi et a/., 1991), the S-layer is composed of more than one protein. In other organisms, such as Aquaspirillum serpens (Kist and Murray, 1984), Clostridium difficile (Kawata et a/., 1984) and B. brevis (Tsuboi et a/., 1986), there appear to be two superimposed S-layers. In other bacteria, including Bacillus stearothermophilus and Campylobacter fetus (Tummuru and Blaser, 1993), more than one S-layer can appear sequentially.…”
Section: Oligonucleotide Probe and Dna Librariesmentioning
confidence: 99%
“…This particularly applies to subunit-subunit interactions, to regions exposed to the environment, and to regions interacting with the underlying cell envelope components. Such a description is becoming possible for several species whose S-layer genes have been cloned and sequenced and for which the possibil-ity for high-resolution image analysis exists (6,7,17,18,30,31). C. crescentus is such a species.…”
mentioning
confidence: 99%
“…The gene encoding the non-glycosylated, hexagonally arranged S-layer of B. stearothermophilus PV72 was cloned and sequenced by Kuen et al (1994). These authors showed sequence comparisons with other signal sequences and found a high degree of homology within signal sequences of extracellular proteins in Bacillus species, such as alkaline phosphatase and neutral protease from B. amyloliquefaciens (Vasantha et al, 1984), as well as the signal sequence for B. sphaericus gene 125 (Bowditch et al, 1989), and the outer-wall protein gene for B. brevis (Tsuboi et al, 1986). Peptide mapping and N-terminal sequencing results strongly indicated that the S-layer protein of B. stearotherrnophilus NRS 2004/3a and two induced variant strains are encoded by different genes and are not derived from a universal precursor form .…”
Section: Genetic Studiesmentioning
confidence: 99%
“…A portion of each of the OWP and MWP (middle-wall protein) genes of B. brevis 47 was cloned in E. coli by an immunological procedure (Tsukagoshi et al, 1984). Analysis of transcripts in B. brevis 47 revealed that the genes for the MWP and OWP constitute a cotranscriptional unit and they are transcribed from multiply and tandemly arranged promoters located upstream of the MWP gene [ c w p (cell-wall protein gene) operon] (Yamagata et al, 1987;Tsuboi et al, 1986). After analysis of the DNA sequence of the promoter region (Yamagata et al, 1987), the complete nucletide sequence of the cwp operon was determined (Tsuboi et al, 1988).…”
Section: Genetic Studiesmentioning
confidence: 99%
See 1 more Smart Citation